Eltűnek Hitt Egykori Premontrei Prépostság az Erdélyi Mezőségen - Gábor, Horváth (Magyar Egyháztörténeti Vázlatok Regnum, 2002)
A One-time Premonstratensian Provostry in the Mezőség ofTransylvania That Was Believed to Have Disappeared
Keywords: sic; 📚 premonstratensian (general)

Hospitalitas en de aanwezigheid van leken in de middeleeuwse premonstratenzer kloosters - Janssens, Herman (Bijdragen van de contactdag, 2002)
Keywords: 📚 premonstratensian (general)

Premonštráti a ich vývoj v stredoveku - Lászlóová, Henrieta (Rehole a kláštory v stredoveku, 2002)
Keywords: 📚 premonstratensian (general)

Die Prämonstratenser - Steffen, Uwe (Lauenburgische Heimat, 2002)
Keywords: 📚 premonstratensian (general)